Ophthalmic Nursing. - Stollery, Rosalind (John Wiley & Sons, 2008)
This third edition of Ophthalmic Nursing reflects recent advances in diagnosis and treatment and developments in the role of the ophthalmic nurse. It includes evidence-based procedures for care of ophthalmic patients on the ward, in outpatients, day care and casualty. The third edition includes more on professional issues and specialist nursing roles, differentiates adult and paediatric issues, and places more emphasis on assessment skills, pain management, infection control, day surgery, psychological aspects and links to primary care. Ophthalmic Nursing is an invaluable resource for all nurs.